Story of Love - Antonius Edi Dwi Purnomo (SELONDING, 2017)
The work of art has the goal of music as a form of application of enculturation as idium cultural phenomenon in the making. Story of Love is a work of art inspired by the journey of love two people who have different cultural backgrounds, the process of melting a man against a culture. This musical artwork has three parts form with the translation of each individual human being into the idea of cultivating to the union of two human beings. This musical artwork using idium tradition as a basic foundation with an emphasis on Java and Minangkabau culture. Methods of augmentation, retrobasi, harmony, and dynamics is the method used in the process of cultivating a work entitled Story of Love. This work is one manifestation of which music is a universal means of communication. This music works also as a form of art conservation teradisi as a form of respect to the local culture.Keywords: cultural phenomenon enculturation, the journey of love, music universal means of communication, cultural preservation.